The Emergence of New States in Eastern Europe in 1918—Lessons for All of Europe - Balcer Adam (TalTech Journal of European Studies, 2021)
The year of 1918 was a crucial point in the history of Europe. Its importance does not only stem from the end of World War I, but also from the establishment of new states. Eastern Europe was particularly an arena where many new states emerged after the dissolution of tsarist Russia. The abovementioned process was correlated with the outcome of World War I (the defeat of the Central Powers on the Western Front and their victory on the Eastern Front against the tsarist Russia resulting in imposing their protectorate over Eastern Europe) but simultaneously it was influenced by the 1917 Bolshevik Revolution originating from a structural crisis of Russia.